2021
DOI: 10.1097/aln.0000000000003820
|View full text |Cite
|
Sign up to set email alerts
|

Combined Platelet and Erythrocyte Salvage: Evaluation of a New Filtration-based Autotransfusion Device

Abstract: Background The SAME device (i-SEP, France) is an innovative filtration-based autotransfusion device able to salvage and wash both red blood cells and platelets. This study evaluated the device performances using human whole blood with the hypothesis that the device will be able to salvage platelets while achieving a erythrocyte yield of 80% and removal ratios of 90% for heparin and 80% for major plasma proteins without inducing signification activation of salvaged cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…Indeed, the obtained treatment rate was higher than 80 mL/min, which is faster than the rate encountered by machines treating blood per centrifugation, even when using the emergency mode [59], and allowed the treatment of 500 mL to 700 mL diluted shed blood in less than 6 minutes. Moreover, platelet yield was always greater than 40% and higher than that obtained in the preliminary in vitro study of i-SEP using human blood [30]. Platelet concentration yields with the i-SEP device is higher than the ones that are usually observed with devices using centrifugation as a concentration method in in vitro and in vivo studies [59].…”
Section: Plos Onementioning
confidence: 78%
See 4 more Smart Citations
“…Indeed, the obtained treatment rate was higher than 80 mL/min, which is faster than the rate encountered by machines treating blood per centrifugation, even when using the emergency mode [59], and allowed the treatment of 500 mL to 700 mL diluted shed blood in less than 6 minutes. Moreover, platelet yield was always greater than 40% and higher than that obtained in the preliminary in vitro study of i-SEP using human blood [30]. Platelet concentration yields with the i-SEP device is higher than the ones that are usually observed with devices using centrifugation as a concentration method in in vitro and in vivo studies [59].…”
Section: Plos Onementioning
confidence: 78%
“…The reinfusion of platelets is considered as a potential prothrombotic risk. However, it was shown that the i-SEP autotransfusion system does not activate platelets during the treatment, and that platelets keep their ability to be activated after the treatment [30]. However, platelet activation was not evaluated in this animal study.…”
Section: Plos Onementioning
confidence: 87%
See 3 more Smart Citations